Rozwiąż poniższe równania:

a) - 1/3x - 0,4 = 3/5 - x + 1 : 2
b) y + 3 (2-y) : 2 = -1/6 + -3-4 : 3
c) x-1 : 2 = 4,6 + 3 1/2x
d) 2,5 - 2 : 2 = 8x + 0,5 : 7
e) x - 5 : 8 = 5x - 18 : 12
f) 4/9x - 2 = 5/12x - 1 1/3
g) 2x - 5 : 3 - 1 = 10,2 + x

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-08T17:38:42+01:00
A) - 1/3x - 0,4 = 3/5 - x + 1 : 2
-⅓x+x=½+3/5+2/5
2/3x=1/2+1
2/3x=3/2
x=3/2*3/2
x=9/4
x=2¼
b) y + 3 (2-y) : 2 = -1/6 + -3-4 : 3
y+(6-3y):2=-1/6 + -3-4/3
y+3-3/2y=-4½
-½y=-4½-3
-½y=-7½ /*(-1)
½y=7½
y=15/2*2
y=15

c) x-1 : 2 = 4,6 + 3 1/2x
x-½-3½x=4,6
x-3½x=4,6+½
-2½x=5,1
x=-51/25
x=-2,04

d) 2,5 - 2 : 2 = 8x + 0,5 : 7
2,3-1=8x+ 1/14
8x=1,3-1/14
8x= 13/10-1/14
8x=182/140-10/140
8x=172/140
x=43/35 *1/8
x=43/280

e) x - 5 : 8 = 5x - 18 : 12
x-5/8=5x-3/2
x-5x=-3/2+5/8
-4x= -12/8+5/8
-4x=-7/8 /*(-1)
4x=7/8
x=7/32

f) 4/9x - 2 = 5/12x - 1 1/3
4/9x-5/12x=-4/3+2
48/108x-45/108x= 2/3
3/108x=2/3
x=2/3*108/3
x=24

g) 2x - 5 : 3 - 1 = 10,2 + x
2x-x=10,2+5/3+1
x=11,2 +5/3
x=112/10+5/3
x=336/30+50/30
x=195/15